Formação de preços no mercado de café - Mesquita, José Marcos Carvalho de (1998)
Based on the evidences ofprices variations paid to coffee producers which varied quite high in these past years, the present research was conducted to verify if coffee market operates close to the competitive model or if rt has endured any manipulative action imposed by any agent that plays a role on it. It was searched a statistical model that could represent significantly theprocess of price formation in this distinct market, at the same time that it was tested the existence of a price transmission causality between the Coffee, Sugar and Cocoa, New York, and Brazilian market ofproducer. The economical theory states that in a perfect competitive market the adjustment between supply and demand will determine the equilibrium price, and on the other hand, if it prevails the conditions ofimperfect market, a monopsony for example, any type ofmanipulation can exist. It can be pointed outtwo characteristics in the coffee market: the oligopsonistic structure which is related to a great number of rural producers and a small number ofintermediary buyers, represented by industries oftoasting and grinding coffee, as well as exporters; the other is the great partnership ofthe commodity in transactions ofthe market and future exchange, done by the agents of the financial market. The procedures used were the Ordinary Least Squares objectiving to estimate a function that could represent the price formation. In the case ofprice transmission, itwas used a causality test which is specific for this purpose. Three tests were done: one for a complete historical serie and two others for the subperiods which presented distinctive characteristics. The results for the price formation model indicate that the variables worldsuppplyanddemand are important to determine the price paidto brazüian producer. Regardingto the causality test, the results indicate absence of causality between the New York market and the Brazüian market in the total period and second subperiod, while in the fírst subperiod it was verified causality towards Brazüian market for the stock exchange. According to these results it was concluded that no confíguration of prices manipulation was identifíed.